Extracellular hypothalamic gamma-aminobutyric acid (GABA) and L-glutamic acid concentrations in response to bicuculline in a genetic absence epilepsy rat model - (:unkn) unknown (JAPANESE PHARMACOLOGICAL SOC, 2008)
The posterior part of the hypothalamus plays a vital role in the homeostatic processes of the internal environment, including blood pressure and heart rate regulation, by means of gamma-aminobutyric acid (GABA)ergic and glutamatergic neurotransmission. In this study we measured the extracellular levels of GABA and L-glutamic acid in the dorsomedial hypothalamic nucleus (DMH) and posterior hypothalamus (PH), following intracerebroventricular (i.c.v.) administration of bicuculline, a GABA(A)-receptor antagonist, in genetic absence epileptic rats from Strasbourg (GAERS), where heart rate, blood pressure, and EEG recordings were also collected simultaneously. The i.c.v. injection of bicuculline (0.3 nmol) produced no response in non-epileptic Wistar rats but caused an increase in mean arterial pressure in GAERS (P < 0.01). Microdialysis experiments showed that L-glutamic acid increased in the DMH in GAERS after bicuculline administration (P < 0.01). Additionally, extracellular GABA concentration decreased in the PH (P < 0.05). Bicuculline suppressed the spike-and-wave discharges, the characteristic sign of absence seizures. All these results suggest that the bicuculline-induced blood pressure response is accompanied by changes in L-glutamic acid levels in the DMH and GABA levels in the PH, indicating a bicuculline hypersensitivity in the DMH and PH of GAERS that may make the GAERS display an altered mode of central cardiovascular regulation. These results suggest that the circuits affected in GAERS are not only restricted to the regions responsible for seizure generation but also present in the hypothalamus.
Keywords: microdialysis; dorsomedial hypothalamic nucleus (DMH); posterior hypothalamus (PH); genetic absence epileptic rats from Strasbourg (GAERS); central cardiovascular regulation; CARDIOVASCULAR-RESPONSES; PARAVENTRICULAR NUCLEUS; POSTERIOR HYPOTHALAMUS; AMYGDALA; SUSCEPTIBILITY; MICRODIALYSIS; DECREASES; RECEPTORS; BLOCKADE